2018
DOI: 10.1186/s13071-018-3036-9
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito microbiota cluster by host sampling location

Abstract: BackgroundMicrobial communities that inhabit the mosquito body play an import role in host biology and may have potential for mosquito control. However, the forces that shape these microbial communities are poorly understood.MethodsTo gain a better understanding of how host location influences the composition and diversity of mosquito microbiota, we performed a survey of microbial communities in mosquito samples collected from six USA states using HiSeq sequencing of the 16S rRNA gene.ResultsA total of 284 bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
61
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 78 publications
11
61
1
Order By: Relevance
“…No major human pathogens transmitted by C. quinquefasciatus have been reported in Grenada, but the mosquito is capable of transmitting several arboviruses that occur in other Caribbean islands (e.g., WNV, St. Louis Encephalitis virus) or in neighboring mainland South American countries (e.g., Wuchereria bancrofti) [17]. The microbial composition of A. aegypti and C. quinquefasciatus mosquitoes has been previously studied [18,19,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. However, several arthropod-borne diseases that are endemic to the mainland Americas are not believed to be established in Caribbean islands (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…No major human pathogens transmitted by C. quinquefasciatus have been reported in Grenada, but the mosquito is capable of transmitting several arboviruses that occur in other Caribbean islands (e.g., WNV, St. Louis Encephalitis virus) or in neighboring mainland South American countries (e.g., Wuchereria bancrofti) [17]. The microbial composition of A. aegypti and C. quinquefasciatus mosquitoes has been previously studied [18,19,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. However, several arthropod-borne diseases that are endemic to the mainland Americas are not believed to be established in Caribbean islands (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…found that sampling site has a strong effect on microbial composition and diversity, even when examining nine different mosquito species [27]. Note however that "collection site" in our study summarizes many parameters.…”
Section: Discussionmentioning
confidence: 69%
“…However, while these laboratory and eld studies highlight the role of the mosquito midgut micro ora in regulating the development and transmission of human pathogens, very little is known about the factors that shape the diversity of the bacterial composition in wild mosquitoes. Some studies have suggested that mosquito collection location is associated with the composition of the microbiota [26,27] while others showed that the microbial composition differed between mosquito species, even when they are closely related and collected at the same location [28], or reared under the same conditions [20]. In addition, there is evidence that resistance to pesticides can be mediated by symbiont bacteria [29,30], and therefore it is possible that genetic resistance to insecticides could also in uence the microbial composition (e.g., resistance would allow exposure of the gut microbiota to insecticides and alter the composition of the microbiota).…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we focus on prokaryotes and eukaryotic microbes. The mosquito gut microbiota is mainly acquired from the environment (Wang et al, 2017;Strand, 2018), and its composition is highly dynamic, varying greatly with species, nutrition, stage of mosquito development, and geography (Tchioffo et al, 2015;Minard et al, 2017;Novakova et al, 2017;Bascunan et al, 2018;Krajacich et al, 2018;Muturi et al, 2018;Telang et al, 2018;Duguma et al, 2019). Sequencing of the 16S rRNA or18S rRNA hypervariable regions is used as a culture-independent approach to study mosquito microbiota composition (Pidiyar et al, 2004;Belda et al, 2017).…”
Section: Gut Microbiota Diversity and Distribution In Mosquitoesmentioning
confidence: 99%
“…Bacteria colonize different mosquito organs, mainly midgut and rarely salivary glands, ovaries and male accessory glands (Tchioffo et al, 2015;Muturi et al, 2018). Most studies have focused on midgut microbiota.…”
Section: Gut Microbiota Diversity and Distribution In Mosquitoesmentioning
confidence: 99%